THE IMPORTANCE OF DEVELOPING CRITICAL THINKING OF TEACHER-STUDENTS OF THE EFL SPHERE (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
The article is devoted to one of the most urgent problems in teaching pedagogical university students – the formation of critical thinking. The basic structural elements of critical thinking are described, without knowledge of which it is impossible to form critical thinking in future teachers. It is emphasized that the basic structural elements are closely interrelated with the intellectual development of the individual. The article analyzes some of the existing definitions of critical thinking; the author's understanding of the content of the concept of "critical thinking of a teacher" is proposed.